Characteristics of pelleted wheat middlings that affect summer storage - Reed, Carl R.; Trigo-Stockli, Dionisia M.; Blasi, Dale A.; Fairchild, Fred J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pelleted wheat middlings samples were collected from four Kansas flour mills in March, April, and May, 1997 to characterize their moisture content and bulk density as they would be purchased directly from the mills by a livestock producer. The average moisture content of pelleted wheat middlings was 14% as they left the mills but declined during the spring to 13.6%. Pellets purchased from Kansas mills during the summer months are likely to contain 13.0 to 13.5% moisture. The average bulk density was approximately 40 lb/ft3 , which is equivalent to about 50 lb/bu. Based on the equilibrium moisture contents determined from the collected samples, if air at typical Kansas summertime temperatures is above 65% relative humidity, pellets will absorb moisture during storage.
Keywords: Beef; Wheat middlings; Storage